External Adjustment and the Global Crisis - Milesi-Ferretti, Gian (IMF Working Papers; Working Paper ;, 2011)
After widening substantially in the period preceding the global financial crisis, current account imbalances across the world have contracted to a significant extent. This paper analyzes the factors underlying this process of external adjustment. It finds that countries whose pre-crisis current account balances were in excess of what could be explained by economic fundamentals have experienced the largest contractions in their external balance. External adjustment in deficit countries was achieved primarily through demand compression, rather than expenditure switching. Changes in other investment flows were the main channel of financial account adjustment, with official external assistance and ECB liquidity cushioning the exit of private capital flows for some countries.